Лексикографічні традиції Б. Д. Грінченка в "Російсько-українському словнику" за редакцією А. Ю. Кримського та С. О. Єфремова - Поздрань, Ю.В. (Лексикографічний бюлетень, 2013)
The article deals with lexicographic tradition embodied in the «Ukrainian Language Dictionary » in 4 volumes edited by B.Grinchenko (1907–1909) in the light of «Russian-Ukrainian Dictionary» edited by A.Crymskiy and S.Yefremov; out approaches to processing registry «Russian-Ukrainian dictionary» and the principles of scientific development entries, dictionary assessed in terms of compliance with established there by the time lexicographical tradition due to formed В.Grinchenko principles laying dictionary.